Physical-mathematical modeling of the vibrating conveyor drying process of soybeans - Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Verkholantseva, Valentyna; Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Kiurcheva, Liudmyla; Кюрчева, Людмила Миколаївна; Кюрчева, Людмила Николаевна; Dumanskyi, Oleksandr (My University, 2020)
The parameters of the operating modes of vibration wave transportation of products for infrared drying were determined under the conditions that allow with the minimum energy consumption to provide the maximum productivity of the apparatus, which takes place in the case of providing the desired reduction of the moisture of the bulk mass for one pass of the product flow with a satisfactory uniformity of production. The implementation of these conditions requires synchronization of the operating parameters of the two vibrators of the vibrating conveyor infrared dryer, which are aggregated in the supporting rolls of the deformed transport element. The article deals with determination of regularities of basic parameter change of the infrared drying process, which allows to determine development tendencies of technical and technological efficiency of mechanization means of the high-temperature storage system of seed material of oil-bearing products, which is solved due to use of innovative vibrating conveyor technologies and equipment in the process of vibration, wave, impulse, and combined physical and mechanical factors that make available minimizing energy and material consumption at maximum output maintaining the properties of agricultural raw materials. These measures are implemented through the development of vibration wave inter-operative transportation under the conditions of soybean infrared drying. According to experimental studies, using the “dimension analysis” method and the Federman-Buckingham theorem the criterion equation of the process of mass transfer during drying in the fluidized bed of products has been obtained, which is determined by the criteria of Péclet, Stanton, Bourdieu, a function that characterizes the energy, heat and mass transfer parameters, the performance of the studied process, which allows to form the recommended series when designing conveyor infrared dryers for storage systems of bulk agricultural products.
Keywords: vibration; drying; soybean; similarity criteria; process; machine